Ti-doped Pd-Au catalysts for one-pot hydrogenation and ring opening of furfural - Date, Nandan Shreehari; La Parola, Valeria; Rode, Chandrashekhar Vasant; Testa, Maria Luisa (Catalysts, 2018)
Pd-Au bimetallic catalysts with different Pd/Au atomic ratios, supported on ordered structured silica (Hexagonal mesoporous silica-HMS, or Santa Barbara Amorphous-15-SBA-15) were evaluated for one-pot hydrogenation of furfural to 1,2-pentanediol. The surface and structural properties of the catalysts were deeply investigated by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), N-2 adsorption isotherms (BET), Infrared spectroscopy (IR), and acid capacity measurements. XPS studies revealed that Ti doped supports had higher dispersion of the active phase, particularly in the case of Pd-Au materials in which Ti played an important role in stabilizing the metallic species. Among the various process conditions studied, such as temperature (160 degrees C), catalyst amount (10% w/w), and reaction time (5 h), H-2 pressure (500 psi) was found to improve the 1,2-pentanediol selectivity. The SBA silica bimetallic Ti-doped system showed the best performance in terms of stability and reusability, after multiple cycles. Under specific reaction conditions, the synergism between Pd-Au alloy and Ti doping of the support allowed the ring opening pathway towards the formation of 1,2-pentanediol in furfural hydrogenation.
Keywords: Bimetallic catalyst; furfural; Hydrogenation; ring-opening